Determinants of Young Work Force Participation in Gig Economy: A Socio-Economic Approach - Inayatullah, Faiz; Fazaalloh, Al Muizzuddin (Journal of Development Economic and Social Studies, 2026)
The rapid expansion of Indonesia's gig economy offers flexibility but obscures structural vulnerabilities faced by young workers. This study analyses the demographic and socio-economic determinants of youth participation (aged 18–30) in the gig economy, examining whether it serves as a voluntary career choice or a survival strategy. Utilizing microdata from the 2024 National Labor Force Survey (SAKERNAS) with a filtered sample of 12,658 individuals, this research employs a binary logistic regression model to estimate participation probabilities. The findings reveal that participation increases with age within the youth bracket and is significantly higher among individuals with lower educational attainment, challenging the assumption that digital work favors the highly educated. Contrary to urban-centric narratives, rural youth demonstrate a higher probability of becoming gig workers due to limited formal opportunities. Furthermore, household heads and divorced individuals are more likely to participate out of economic necessity, while gender is statistically insignificant. The study concludes that for many Indonesian youth, the gig economy functions as an involuntary fallback option and survival mechanism rather than a path to professional autonomy, implying that formal diplomas are increasingly replaced by algorithmic compliance and digital signalling for vulnerable demographics.